(3ebQC fGaY Hf YHO GdQMef GdeOfis - (3eMeO Hf CMeO Hf jhSa Hf ehSi, CHh YHO Gddgs ((3ehSi Hf jhSa Hf ehSi Hf jhSa s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg Mb MeOg SCdfi ef jMH GdfXQ ai bQGAI CHj fYje fGaY Hf YHO GdQMef Cf GaQOgG dg Yf ZjQgG , hGHjf dg ef GUhdgG eG jLH GdfXQ ajg hGdhbha Ydjg s
(3BNQgG (B:s
(3aGYde Pdc hJMbbg hQGY GdCUhd GdJi PcQfGgG , aYdjgG MaX LejY GdCUhd jYde Pdc Cgd GdYde hGdJage Je GdcJGH HYhf Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs